One-Pot method for the selective conversion of hemicellulose from crop waste into C5 sugars and furfural by using solid acid catalysts - Sahu, Ramakanta; Dhepe, Paresh Laxmikant (Chemsuschem, 2012)
We present a solid-acid catalyzed one-pot method for the selective conversion of solid hemicellulose without its separation from other lignocellulosic components, such as cellulose and lignin. The reactions were carried out in aqueous and biphasic media to yield xylose, arabinose, and furfural. To overcome the drawbacks posed by mineral acid methods in converting hemicelllulose, we used heterogeneous catalysts that work at neutral pH. In a batch reactor, these heterogeneous catalysts, such as solid acids (zeolites, clays, metal oxides etc.), resulted in >90% conversion of hemicellulose. It has been shown that the selectivity for the products can be tuned by changing the reaction conditions, for example, a reaction carried out in water at 170 degrees C for 1 h with HBeta (Si/Al=19) and HUSY (Si/Al=15) catalysts gave yields of 62 and 56% for xylose and arabinose, respectively. With increased reaction time (6 h) and in presence of only water, HUSY resulted in yields of 30% xylose+arabinose and 18% furfural. However, in a biphasic reaction system (water+p-xylene, 170 degrees C, 6 h) yields of 56% furfural with 17% xylose+arabinose could be achieved. It was shown that with the addition of organic solvent the furfural yield could be increased from 18 to 56%. Under optimized reaction conditions, >90% carbon balance was observed. The study revealed that catalysts were recyclable with a 20% drop in activity for each subsequent run. It was observed that temperature, pressure, reaction time, substrate to catalyst ratio, solvent, and so forth had an effect on product formation. The catalysts were characterized by means of X-ray diffraction, temperature-programmed desorption of NH3, inductively coupled plasma spectroscopy, elemental analysis, and solid-state NMR (Si-29, Al-27) spectroscopy techniques.
Keywords: analytical methods; Biomass; carbohydrates; heterogeneous catalysis; zeolites